Comparing random coefficient autoregressive model with and without autocorrelated errors by Bayesian analysis - Autcha Araveeporn (My University, 2016)
We proposed a Bayesian analysis for estimating an unknown parameter in a Random Coefficient Autoregressive (RCA) model and its AutoRegressive (AR) process errors. We called this model an RCA model with autocorrelated errors (RCA-AR). A Markov Chain M
Keywords: Statistical Methods and Inference